Listen for the whisperer - Whitney, Phyllis A., 1903- (Garden City, N.Y. ; Doubleday, 1971)
Leigh honors her father's deathbed request to travel to Norway and search out her mother, a great actress whom the girl has known only as a distant, romantic figure.
Keywords: Norway -- Fiction; Romantic suspense fiction